β-Aminopropionitrile-Induced Reduction in Enzymatic Crosslinking Causes In Vitro Changes in Collagen Morphology and Molecular Composition - Canelón, Silvia P.; Wallace, Joseph M. (PLOS ONE, 2016)
Type I collagen morphology can be characterized using fibril D-spacing, a metric which describes the periodicity of repeating bands of gap and overlap regions of collagen molecules arranged into collagen fibrils. This fibrillar structure is stabilized by enzymatic crosslinks initiated by lysyl oxidase (LOX), a step which can be disrupted using β-aminopropionitrile (BAPN). Murine in vivo studies have confirmed effects of BAPN on collagen nanostructure and the objective of this study was to evaluate the mechanism of these effects in vitro by measuring D-spacing, evaluating the ratio of mature to immature crosslinks, and quantifying gene expression of type I collagen and LOX. Osteoblasts were cultured in complete media, and differentiated using ascorbic acid, in the presence or absence of 0.25mM BAPN-fumarate. The matrix produced was imaged using atomic force microscopy (AFM) and 2D Fast Fourier transforms were performed to extract D-spacing from individual fibrils. The experiment was repeated for quantitative reverse transcription polymerase chain reaction (qRT-PCR) and Fourier Transform infrared spectroscopy (FTIR) analyses. The D-spacing distribution of collagen produced in the presence of BAPN was shifted toward higher D-spacing values, indicating BAPN affects the morphology of collagen produced in vitro, supporting aforementioned in vivo experiments. In contrast, no difference in gene expression was found for any target gene, suggesting LOX inhibition does not upregulate the LOX gene to compensate for the reduction in aldehyde formation, or regulate expression of genes encoding type I collagen. Finally, the mature to immature crosslink ratio decreased with BAPN treatment and was linked to a reduction in peak percent area of mature crosslink hydroxylysylpyridinoline (HP). In conclusion, in vitro treatment of osteoblasts with low levels of BAPN did not induce changes in genes encoding LOX or type I collagen, but led to an increase in collagen D-spacing as well as a decrease in mature crosslinks.